2018
DOI: 10.1016/j.jtumed.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Biological investigation of novel metal complexes of 2-amino-4-substituted phenylthiazole Schiff bases

Abstract: Objective Invasive microorganisms and free radicals are responsible for the delayed healing of various infections. It is necessary to discovery of novel molecules that are effective against invasive microorganisms and inhibit free radicals. Therefore, a series of metal complexes of 2-amino-4-substituted phenylthiazole Schiff bases were synthesized. Methods Structural characterization of the synthesized molecules was performed by elemental analysis, FT/IR, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Some literature indicated that the metal complex formation between transition metals like cobalt, nickel, zinc, copper, and drug molecule significantly improves the drug's biological function [ 239 , 240 ]. As an explanation, the metal complex serves as a vehicle for drug ligand, and the bond between the metal and ligand cleaves easily inside the body leading to accelerated drug action and increased efficacy [ 241 , 242 ].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…Some literature indicated that the metal complex formation between transition metals like cobalt, nickel, zinc, copper, and drug molecule significantly improves the drug's biological function [ 239 , 240 ]. As an explanation, the metal complex serves as a vehicle for drug ligand, and the bond between the metal and ligand cleaves easily inside the body leading to accelerated drug action and increased efficacy [ 241 , 242 ].…”
Section: Plant-derived Compoundsmentioning
confidence: 99%
“…[13] A large number of metal complexes synthesized so far with various oxygen, nitrogen, sulfur or combined ligands have shown antitumor, antibacterial, antifungal, antituberculous and antihypertensive effects. [14][15][16][17] In addition, complexes are now being studied as potential synthetic antioxidants and yielding promising results in in vitro and in vivo studies.…”
Section: Metal Complexesmentioning
confidence: 99%
“…New ligands in coordination chemistry were gave new importance in inorganic chemistry field represented by Azo compounds are Containing (-N=N-) group (1) , The presence of the unshared electron pair on the nitrogen atom made these compounds of great importance in many areas as a result of the effectiveness shown by these compounds and their derivatives (2) . It have significant importance for construction of this well-defined architecture because it used as antibacterial (3) , anticancer (4) and antimicrobial evaluation in medicinal and pharmaceutical fields (5)(6) . Also Schiff bases of chelating compounds containing a group (N=C-) with high activity (7) , and its derivatives of 4aminoantipyrine and its complexes have wide applications both in the medical field, pharmaceutical (8) ,as antitoxtante (9) ,,antioxidant (10) chemical stimulation (11) , in addition to their physiological applications as ,and impartment as antibacterial (12) and antifungal (13) .…”
Section: Introductionmentioning
confidence: 99%